DAMPAK FLEKSIBILITAS, LIKUIDITAS, UKURAN, DAN STRUKTUR ASET PADA STRUKTUR MODAL - Enjelita Oktaviani Siringoringo; Nurseto Adhi; Edi Wijayanto; Arum Febriyanti Ciptaningtias; Gunawan R Setianegara; Winarni Winarni; Muhamad Sidik (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of financial flexibility, liquidity, firm size, and asset structure on capital structure in coal companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research employs quantitative secondary data derived from the financial reports of 11 companies, totaling 44 observations. The dependent variable is the Debt Asset Ratio (DAR), while the independent variables include financial flexibility, liquidity, firm size, and asset structure. Data analysis is conducted using multiple linear regression with a Fixed Effect Model (FEM) approach. The findings reveal that financial flexibility has a significant negative effect on capital structure, indicating that companies with high financial flexibility tend to reduce debt usage. Firm size also has a significant negative impact on capital structure, showing a preference for internal financing among larger firms. In contrast, liquidity and asset structure do not significantly affect capital structure. High liquidity does not reduce reliance on debt, while low asset structure fails to provide adequate collateral for borrowing. These results contribute to corporate financial management, particularly in determining optimal capital structure policies based on firm characteristics. The study also reaffirms the pecking order theory as a basis for financing decisions.